TRIM29 in Cutaneous Squamous Cell Carcinoma - Hsu, Che-Yuan; Yanagi, Teruki; Ujiie, Hideyuki (Frontiers in Medicine, 2021)
Tripartite motif (TRIM) proteins play important roles in a wide range of cell physiological processes, such as signal transduction, transcriptional regulation, innate immunity, and programmed cell death. TRIM29 protein, encoded by the ATDC gene, belongs to the RING-less group of TRIM protein family members. It consists of four zinc finger motifs in a B-box domain and a coiled-coil domain, and makes use of the B-box domain as E3 ubiquitin ligase in place of the RING. TRIM29 was found to be involved in the formation of homodimers and heterodimers in relation to DNA binding; additional studies have also demonstrated its role in carcinogenesis, DNA damage signaling, and the suppression of radiosensitivity. Recently, we reported that TRIM29 interacts with keratins and FAM83H to regulate keratin distribution. Further, in cutaneous SCC, the expression of TRIM29 is silenced by DNA methylation, leading to the loss of TRIM29 and promotion of keratinocyte migration. This paper reviews the role of TRIM family proteins in malignant tumors, especially the role of TRIM29 in cutaneous SCC.